High-flexibility nano-porous bimetallic copper-nickel alloy-copper-nickel oxide material as well as preparation method and application thereof

By using nanoporous bimetallic copper-nickel alloy-copper-nickel oxide materials, using the combination of copper-nickel-based amorphous alloy and nanoporous bimetallic copper-nickel alloy-copper-nickel oxide layers, and preparing in one-step electrochemical dealloyment method, the problems of poor flexibility and poor electrochemical performance of supercapacitor electrode materials are solved, and electrode materials with high flexibility and excellent electrochemical performance are achieved.

CN119852098APending Publication Date: 2025-04-18HUANGHUAI UNIV

Patent Information

Application Number
CN202510070040.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Currently, copper-nickel oxide-based electrode materials for supercapacitors have problems with poor flexibility and poor electrochemical performance.

Method used

High flexibility nanoporous bimetallic copper-nickel alloy-copper-nickel oxide material is used, which consists of copper-nickel-based amorphous alloy and nanoporous bimetallic copper-nickel alloy-copper-nickel oxide layer. It is prepared by one-step electrochemical dealloyment method to form a 3D bicontinuous nanoporous structure.

Benefits of technology

The high flexibility and excellent electrochemical properties of the electrode material are achieved, and can be used in wearable electronic products. The preparation process is simple and efficient, with high repeatability and reproducibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852098A_ABST
    Figure CN119852098A_ABST
Patent Text Reader

Abstract

The invention discloses a high-flexibility nano-porous bimetallic copper-nickel alloy-copper-nickel oxide material and a preparation method and application thereof, and belongs to the technical field of capacitor electrode materials. The material is composed of a copper-nickel-based amorphous alloy and a nano-porous bimetallic copper-nickel alloy-copper-nickel oxide layer. The copper-nickel-based amorphous alloy is used as a middle core layer, so that excellent flexibility is provided for the electrode; nano-porous bimetallic copper nickel-copper nickel oxide layers are arranged on the two sides of the middle core layer and are used for providing an electroactive material for the electrode; the component of the copper-nickel-based amorphous alloy is Ti < x > Ni < x > Cu < 50-x > Zr < 50-x >, the subscript is the atomic percentage of each element, and x is 25-40. The method has the beneficial effects of convenience, rapidness, simplicity and high efficiency. The nickel-copper oxide electroactive material can be prepared only through an electrochemical dealloying one-step method, the synthesis condition is mild, the cost is low, the electrochemical dealloying current is easy to control, and the prepared electrode has high repeatability and reproducibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of capacitor electrode materials, and in particular relates to a high-flexibility nanoporous bimetallic copper-nickel alloy-copper-nickel oxide material and a preparation method and application thereof. Background Art

[0002] The energy storage characteristics of supercapacitors are the key factors restricting their promotion and application, and the performance of their electrode materials determines the energy storage characteristics. Therefore, the research and development of electrode materials with excellent performance is crucial to improving the energy storage characteristics of supercapacitors. Although various carbon-based porous materials, such as activated carbon, carbon gel and carbon nanomaterials, have been partially commercialized as supercapacitor electrode materials. However, due to the influence of the electrolyte ion adsorption / desorption energy storage mechanism, its specific capacitance value is low and far from meeting the needs of modern electronic products. Researchers have further developed pseudocapacitive electrode materials based on Faraday fast redox reaction energy storage, which has greatly improved the energy density of supercapacitors to the farad level (F). Transition metal oxides - nickel oxide (NiO), copper-based oxides (CuxO, x = 1, 2), etc. have high theoretical specific capacity and cycle stability, and they are low in price, abundant in resources, and environmentally friendly. They are widely valued and are expected to become a new generation of high-quality supercapacitor electrode materials. However, most of the transition metal oxides prepared at present are powder electrode materials, which need to be mixed with conductive agents and binders into slurry, and then coated on the current collector and pressed into electrode sheets by a tablet press. The dense and disordered electrode materials prepared by this coating method do not have continuous electron / ion transmission efficiency and cannot meet the requirements of fast Faraday redox reaction on the surface of electrode materials.

[0003] Therefore, many researchers are committed to developing self-supporting electrodes by directly combining electroactive materials with conductive substrates to avoid the use of conductive agents and adhesives. For example, the research group of Professor Junlei Qi of Harbin Institute of Technology used a three-step method of "chemical oxidation-high temperature carbonization treatment-hydrothermal reaction" to synthesize a core-core-shell structured NiO-C-Cu2O nanorod array self-supporting electrode on copper foam, which exhibited excellent specific capacitance and cycle life (Ceramics International 43 (2017) 15410-15417). Yidong Miao et al. of China University of Mining and Technology (Xuzhou) used commercial copper foil as a substrate, firstly prepared nickel-zinc alloy by electrodeposition in a mixture of zinc nitrate, nickel nitrate and boric acid, then prepared nickel-copper-zinc alloy film by high temperature alloying, then chemically dealloyed to remove zinc, and finally prepared spherical Cu2O / NiO self-supporting electrodes by thermal oxidation (Materials Letters 265 (2020) 127300). Obviously, there are great drawbacks in the preparation methods of these copper-nickel oxides. For example, there are many preparation steps, the process is cumbersome, and the repeatability and reproducibility of the electrode materials are poor; the hydrothermal synthesis requires high temperature and high pressure, and the material crystallinity is poor; the electrodeposited material is not firmly bonded to the substrate and is easy to fall off, etc. These disadvantages are not conducive to the large-scale production of electrode materials.

[0004] The Chinese patent application document with publication number CN104475753A discloses a method for preparing graphene-supported nano copper-nickel alloy (Cu3.8Ni). In the patent, graphene oxide is first prepared, and then CuSO4·5H2O solution, NiSO4·6H2O solution, NaOH solution and hydrazine hydrate solution are mixed with graphene oxide to obtain graphene-supported nano Cu3.8Ni alloy. The patent only prepares graphene-supported nano Cu3.8Ni alloy, and does not further synthesize copper-nickel oxide-based supercapacitor electrode materials, so it cannot be directly used as a supercapacitor electrode. Summary of the invention

[0005] The technical problem to be solved by the present invention is how to solve the problems of poor flexibility and poor electrochemical performance of the current copper-nickel oxide-based electrode materials for supercapacitors.

[0006] The present invention solves the above technical problems through the following technical means:

[0007] The first aspect of the present invention provides a highly flexible nanoporous copper-nickel-copper-nickel oxide material, which is composed of a copper-nickel-based amorphous alloy and a nanoporous bimetallic copper-nickel alloy-copper-nickel oxide layer; the copper-nickel-based amorphous alloy is used as an intermediate core layer (providing excellent flexibility for the electrode); nanoporous bimetallic copper-nickel-copper-nickel oxide layers are provided on both sides of the intermediate core layer (providing electroactive materials for the electrode); the composition of the copper-nickel-based amorphous alloy is Ti x Ni x Cu 50-x Zr 50-x , wherein the subscripts are the atomic percentages of the elements, and x is 25 to 40; the bimetallic copper-nickel alloy is a Cu3.8Ni alloy, and the composition of the copper-nickel oxide is a mixture of NiO and Cu2O.

[0008] Preferably, the thickness ratio of the copper-nickel based amorphous alloy to the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide layer is (2-3):1.

[0009] The second aspect of the present invention provides a method for preparing the above-mentioned highly flexible nanoporous bimetallic copper-nickel alloy-copper-nickel oxide material, comprising the following steps:

[0010] (1) Preparation of copper-nickel based amorphous alloy strips:

[0011] According to the composition of the copper-nickel-based amorphous alloy, Ni, Cu, Zr and Ti metals are mixed and smelted evenly to obtain a Ti-Ni-Cu-Zr alloy ingot; the obtained alloy ingot is heated to a molten state, and the alloy liquid is blown out by an inert gas, so that the molten liquid metal solidifies on a rotating copper roller to obtain a copper-nickel-based amorphous alloy strip;

[0012] (2) Preparation of nanoporous bimetallic nickel-copper alloy-nickel-copper oxide by electrochemical dealloying:

[0013] The nickel-copper based amorphous alloy strip is placed in an acid solution for electrochemical dealloying, and then taken out for cleaning to obtain the alloy.

[0014] Preferably, the purity of the Ni, Cu, Zr and Ti metals is 99.9 wt.%. Preferably, the rotation speed of the copper roller is 34-36 m / s.

[0015] Preferably, the copper-nickel-based amorphous alloy strip has a thickness of 20 to 50 μm and a width of 1.5 to 2 cm.

[0016] Preferably, the acid solution is a mixture of H3PO4 and NH3F, wherein the concentration of NH3F is 0.2-0.5M, the concentration of H3PO4 is 0.2-0.5M; and the molar ratio of H3PO4 to NH3F is 1:1.

[0017] Preferably, the electrochemical dealloying adopts a three-electrode system, wherein the nickel-copper based amorphous alloy strip, Ag / AgCl and platinum mesh are used as the working electrode, the reference electrode and the counter electrode respectively, and the dealloying current density is 5-20 mA cm -2 The dealloying time is 30 to 120 minutes.

[0018] Preferably, the dealloying current density is 10 mA cm -2 , the dealloying time is 60min.

[0019] The third aspect of the present invention proposes the use of the above-mentioned highly flexible nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material as a supercapacitor electrode material.

[0020] The beneficial effects of the present invention are:

[0021] (1) The method of the present invention is convenient, fast, simple and efficient. The present invention only requires a one-step electrochemical dealloying method to prepare the nickel-copper oxide electroactive material. The synthesis conditions are mild and the cost is low. Moreover, the electrochemical dealloying current is easy to control, and the prepared electrode has high repeatability and reproducibility.

[0022] (2) Using amorphous alloy as dealloying precursor breaks through the limitation of internal structural defects of traditional crystalline solid solution alloys. The present invention creatively designs and prepares Ti-Ni-Cu-Zr amorphous alloy strips, which have uniform internal chemical composition, no metallurgical defects such as grain boundaries and segregation, and can easily obtain a large-area uniform nanoporous structure after electrochemical dealloying.

[0023] (3) The electrode has excellent flexibility and can be used in the field of wearable electronic products. A certain thickness of high-strength and tough Ti-Ni-Cu-Zr amorphous alloy core layer can be retained by controlling the dealloying time. The amorphous alloy core layer not only supports the electrode but also gives the electrode excellent flexibility. At the same time, the use of non-electroactive materials such as conductive agents and adhesives is avoided.

[0024] (4) The 3D bicontinuous nanoporous structure greatly increases the specific surface area of ​​the electrode material. The method of the present invention utilizes the principle that Cu and Ni elements can be infinitely soluble in each other at room temperature and that nickel elements can be slightly soluble in an acidic solution containing fluorine ions. The relatively active zirconium and titanium elements and a small amount of nickel elements are preferentially corroded by an electrochemical method in a mixed acid solution to obtain a Cu3.8Ni bimetallic alloy with a 3D bicontinuous nanoporous structure, the ligament size of which is 30 to 70 nm, which increases the specific surface area of ​​the electrode material and is beneficial to improving the electrochemical energy storage performance of the electrode.

[0025] (5) Nanoporous metals have high specific surface energy, and inert components are easily oxidized to form electroactive materials. The electroactive nickel-copper oxide material is formed by in-situ self-oxidation of the alloy ligaments. It is evenly distributed on the surface of the metal ligaments, and the bond with the metal ligaments is extremely strong, without agglomeration or shedding.

[0026] (6) So far, there has been no report on the preparation of nanoporous bimetallic Cu3.8Ni alloys using a one-step dealloying method. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a scanning electron microscope photograph of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material prepared in Example 1.

[0028] Figure 2 This is a surface scanning energy spectrum analysis diagram of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material prepared in Example 1.

[0029] Figure 3 The Ti prepared in Example 1 30 Ni 30 Cu 20 Zr 20 XRD patterns of the strip before and after dealloying.

[0030] Figure 4 This is a bending photograph of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material prepared in Example 1.

[0031] Figure 5 This is the constant current charge and discharge curve of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material prepared in Example 1.

[0032] Figure 6 This is a scanning electron microscope photograph of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material prepared in Comparative Example 1.

[0033] Figure 7 This is a scanning electron microscope photograph of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.

[0036] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.

[0037] Embodiment 1:

[0038] A highly flexible nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material, which is composed of a copper-nickel-based amorphous alloy and a nanoporous bimetallic copper-nickel alloy-copper-nickel oxide; the copper-nickel-based amorphous alloy serves as an intermediate core layer to support the electrode, and the two sides are nanoporous copper-nickel alloys. The surface of the bimetallic copper-nickel ligament is naturally oxidized and uniformly loaded with copper-nickel oxide. The composition of the copper-nickel-based amorphous alloy is Ti x Ni x Cu 50-x Zr 50-x , where the subscripts are the atomic percentages of the elements, and x = 30 at.%.

[0039] The preparation method comprises the following steps:

[0040] The first step is to prepare copper-nickel based amorphous alloy strips

[0041] According to the target alloy Ti 30 Ni 30 Cu 20 Zr 20 The atomic percentage of each element in the master alloy is 99.9wt.% of pure Ti 4.565g, pure Ni 5.596g, pure Cu 4.039g and pure Zr 5.799g, respectively, and 20g of the master alloy raw material is mixed. Then the mixed metal raw materials are placed in a vacuum arc furnace. 20g of pure Ti with a purity of 99.9wt.% is placed in the vacuum arc furnace independently without contacting with the master alloy raw material. Pure titanium is melted first before each smelting as a deoxidizing material. Under the protection of argon, the master alloy is repeatedly smelted 4 times, each time for about 1 minute to ensure the uniformity of the alloy structure. After the smelting is completed, the furnace is cooled to room temperature to obtain Ti. 30 Ni 30 Cu 20 Zr 20 Alloy ingot.

[0042] The alloy ingot obtained after smelting was descaled and cut into suitable sizes, placed in a quartz tube and cleaned with anhydrous ethanol. Amorphous alloy ribbons were prepared using a vacuum spinning machine. The preparation parameters were: vacuum degree 9.0×10 - 4 Pa, blowing pressure 0.1MPa, copper roller surface speed 36m s-1 The master alloy was placed in a quartz tube, heated to a molten state under an argon protective atmosphere, and blow-cast to form an amorphous alloy strip, thereby preparing a silver-containing nickel-based amorphous alloy strip with a thickness of 20 μm and a width of 2 mm;

[0043] The second step is to prepare nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material by dealloying

[0044] Prepare a mixture of 0.25M NH4F and 0.25M H3PO4, cut off 5cm of the copper-nickel-based amorphous alloy strip, immerse it in the mixture for 2cm, and use the remaining 3cm strip as the electrode lead. At room temperature, the strip was electrochemically dealloyed in a three-electrode system with a current density of 10mA cm -2 The dealloying time was set at 60 min, and then the sample was taken out and rinsed repeatedly with deionized water for 3 times to obtain a nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material.

[0045] In order to detect the electrochemical properties of the prepared electrode materials, an electrochemical workstation was used to test its constant current charge and discharge performance in a three-electrode system. The test electrolyte was 2 mol L -1 The KOH solution was used, the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material prepared above was used as the working electrode, the platinum mesh electrode was used as the auxiliary electrode, and the Ag / AgCl electrode was used as the reference electrode. The current density of the constant current charge and discharge was 1A cm -3 , the voltage window is 0~0.45V.

[0046] The scanning electron microscope photo of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material in this embodiment is shown in FIG. Figure 1 As shown, the ligaments of the nanoporous bimetallic copper-nickel alloy prepared in this embodiment are slightly granular and tend to aggregate into a typical "worm shape". The average size of the ligaments is 40nm and the pore size is about 60nm. This 3D bicontinuous nanoporous structure greatly improves its electrochemistry.

[0047] The surface scanning energy spectrum analysis diagram of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material in this embodiment is as follows: Figure 2 As shown, strong peaks of copper, nickel and oxygen appeared in the figure, indicating that the nanoporous bimetallic nickel-copper ligament prepared in this example self-oxidized during the dealloying process to form copper-nickel metal oxide electroactive materials.

[0048] The Ti prepared in this example 30 Ni 30 Cu 20 Zr 20 The XRD patterns of the strip before and after dealloying are shown in Figure 3As shown in the figure, the strip before dealloying only shows a wider "steamed bun peak", which confirms that Ti was prepared by the copper wheel spinning method. 30 Ni 30 Cu 20 Zr 20 The strip is amorphous. After dealloying, obvious peaks of Cu2O and Cu3.8Ni alloy appeared in the figure, indicating that the Zr and Ti elements on the surface of the strip were selectively dissolved during the electrochemical dealloying process, and the electrochemical dealloying process was accompanied by the self-oxidation of copper and nickel. At the same time, the presence of some amorphous bun peaks indicates that the electrode retains a certain amorphous core layer, giving the electrode structural integrity. Figure 2 From the energy spectrum of the medium-nanoporous bimetallic copper-nickel alloy, it can be seen that after dealloying, the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material was successfully prepared.

[0049] The macroscopic deformation photograph of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material in this embodiment is shown in FIG. Figure 4 As shown, the electrode can be bent manually, confirming the excellent flexibility of the electrode material.

[0050] The constant current charge and discharge curve of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material in this embodiment is as follows: Figure 5 As shown in Figure 2, the charge and discharge platforms can be clearly seen from the curve, which correspond to the oxidation reaction and reduction reaction of nickel copper oxide, respectively, indicating its pseudocapacitive characteristics. -3 The specific capacitance is as high as 1100.2F cm at the current density -3 .

[0051] Embodiment 2:

[0052] A method for preparing a highly flexible nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material, comprising the following steps: a first step of preparing a copper-nickel-based amorphous alloy strip

[0053] According to the target alloy Ti 35 Ni 35 Cu 15 Zr 15The atomic percentage of each element in the master alloy is 99.9wt.% of pure Ti 5.538g, pure Ni 6.789g, pure Cu 3.150g and pure Zr 4.522g, respectively, and 20g of the master alloy raw material is obtained by mixing. Then the mixed metal raw materials are placed in a vacuum arc furnace. 20g of pure Ti with a purity of 99.9wt.% is placed in the vacuum arc furnace independently without contacting with the master alloy raw material. Pure titanium is first smelted before each smelting as a deoxidizing material. Under the protection of argon, the master alloy is smelted 4 times, each time for about 1 minute, to ensure the uniformity of the alloy structure. After the smelting is completed, the furnace is cooled to room temperature to obtain Ti. 35 Ni 35 Cu 15 Zr 15 Alloy ingot.

[0054] The alloy ingot obtained after smelting was descaled and cut into suitable sizes, placed in a quartz tube and cleaned with anhydrous ethanol. Amorphous alloy ribbons were prepared using a vacuum spinning machine. The preparation parameters were: vacuum degree 9.0×10 - 4 Pa, blowing pressure 0.1MPa, copper roller surface speed 36m s -1 The master alloy was placed in a quartz tube, heated to a molten state under an argon protective atmosphere, and blow-cast to form an amorphous alloy strip, thereby preparing a silver-containing nickel-based amorphous alloy strip with a thickness of 25 μm and a width of 2 mm;

[0055] The second step is to prepare nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material by dealloying

[0056] Prepare a mixture of 0.30M NH4F and 0.30M H3PO4, cut off 5cm of the copper-nickel-based amorphous alloy strip, immerse it in the mixture for 2cm, and use the remaining 3cm strip as the electrode lead. At room temperature, the strip was electrochemically dealloyed in a three-electrode system with a current density of 15mA cm -2 The dealloying time was set at 90 min, and then the sample was taken out and rinsed repeatedly with deionized water for 3 times to obtain a nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material.

[0057] In order to detect the electrochemical properties of the prepared electrode materials, an electrochemical workstation was used to test its constant current charge and discharge performance in a three-electrode system. The test electrolyte was 2 mol L -1 The KOH solution was used, the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material prepared above was used as the working electrode, the platinum mesh electrode was used as the auxiliary electrode, and the Ag / AgCl electrode was used as the reference electrode. The current density of the constant current charge and discharge was 1A cm -3 , the voltage window is 0~0.45V.

[0058] The nanoporous bimetallic copper-nickel alloy prepared in this embodiment has an average ligament size of 52 nm and an average pore size of 65 nm, and the copper-nickel oxide electroactive material is evenly loaded on the ligament surface.

[0059] The electrochemical performance of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material in this embodiment was tested. The results showed that: -3 At a current density of 1.38 W, the specific capacitance reaches 1206.3 F cm -3 .

[0060] Embodiment 3:

[0061] A method for preparing a highly flexible nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material comprises the following steps:

[0062] The first step is to prepare a copper-nickel-based amorphous alloy strip

[0063] According to the target alloy Ti 40 Ni 40 Cu 10 Zr 10 The atomic percentage of each element in the master alloy is 99.9wt.% of pure Ti 6.592g, pure Ni 8.081g, pure Cu 2.187g and pure Zr 3.140g, respectively, and 20g of the master alloy raw material is obtained by mixing. Then the mixed metal raw materials are placed in a vacuum arc furnace. 20g of pure Ti with a purity of 99.9wt.% is placed in the vacuum arc furnace independently without contacting with the master alloy raw material. Pure titanium is melted first before each smelting as a deoxidizing material. Under the protection of argon, the master alloy is repeatedly smelted 4 times, each time for about 1 minute, to ensure the uniformity of the alloy structure. After the smelting is completed, the furnace is cooled to room temperature to obtain Ti. 40 Ni 40 Cu 10 Zr 10 Alloy ingot.

[0064] The alloy ingot obtained after smelting was descaled and cut into suitable sizes, placed in a quartz tube and cleaned with anhydrous ethanol. Amorphous alloy ribbons were prepared using a vacuum spinning machine. The preparation parameters were: vacuum degree 9.0×10 - 4 Pa, blowing pressure 0.1MPa, copper roller surface speed 36m s -1 The master alloy was placed in a quartz tube, heated to a molten state under an argon protective atmosphere, and blow-cast to form an amorphous alloy strip, thereby preparing a silver-containing nickel-based amorphous alloy strip with a thickness of 25 μm and a width of 2 mm;

[0065] The second step is to prepare nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material by dealloying

[0066] Prepare a mixture of 0.5M NH4F and 0.5M H3PO4, cut off 5cm of the copper-nickel-based amorphous alloy strip, immerse it in the mixture for 2cm, and use the remaining 3cm strip as the electrode lead. At room temperature, the strip was electrochemically dealloyed in a three-electrode system with a current density of 5mA cm -2 The dealloying time was set at 30 min, and then the sample was taken out and rinsed repeatedly with deionized water for 3 times to obtain a nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material.

[0067] In order to detect the electrochemical properties of the prepared electrode materials, an electrochemical workstation was used to test its constant current charge and discharge performance in a three-electrode system. The test electrolyte was 2 mol L -1 The KOH solution was used, the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material prepared above was used as the working electrode, the platinum mesh electrode was used as the auxiliary electrode, and the Ag / AgCl electrode was used as the reference electrode. The current density of the constant current charge and discharge was 1A cm -3 , the voltage window is 0~0.45V.

[0068] The nanoporous bimetallic copper-nickel alloy prepared in this embodiment has an average ligament size of 30 nm and an average pore size of 36 nm, and the surface of the ligament is evenly loaded with copper-nickel oxide electroactive materials.

[0069] The electrochemical performance of the nanoporous bimetallic copper-nickel alloy copper-nickel oxide electrode material in this embodiment was tested. The results showed that: -3 At a current density of 1.38 W, the specific capacitance reaches 986.32 F cm -3 .

[0070] Comparative Example 1:

[0071] The prepared nickel-copper-based amorphous alloy was chemically dealloyed in a free state, and other conditions were the same as those in Example 1. The scanning electron microscopy results showed that no 3D bicontinuous nanoporous structure appeared on the surface of the electrode material, and only a few corrosion pits were sporadically present on the surface, such as Figure 6 This shows that this amorphous alloy is more corrosion-resistant and difficult to directly chemically dealloy in a free state.

[0072] Comparative Example 2:

[0073] The prepared copper-nickel based amorphous alloy strip was electrochemically dealloyed in a mixture of 0.1M NH3 and 0.1M H3PO4. Other conditions were the same as those in Example 1. The SEM results showed that only some nickel-copper alloy particles appeared on the surface of the electrode material, and they did not aggregate into a worm-like ligament structure. The electrochemical test found that the electrode had a high conductivity at 1A cm -3At a current density of 1.38 W, the specific capacitance is only 253.6 F cm -3 .

[0074] Comparative Example 3:

[0075] The prepared copper-nickel based amorphous alloy strip was electrochemically dealloyed in a mixture of 1M NH3 and 1M H3PO4, and other conditions were the same as those in Example 2. The SEM results showed that a large number of corrosion microcracks appeared on the surface of the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material, such as Figure 7 This indicates that the concentration of the etching solution is too high, the corrosion rate is accelerated, and the surface of the electrode material shrinks too much, resulting in corrosion microcracks. In addition, the thickness of the amorphous core layer of the electrode is too small and it is very easy to break.

[0076] Comparative Example 4:

[0077] The target alloy is a Ti-Ni-Cu-Zr amorphous alloy with x=24 at.% or less. Other conditions are the same as those in Example 3. It is found that the amorphous alloy strips just thrown out are brittle and easy to break. After dealloying, the samples are corroded and broken into small pieces, and the mechanical integrity of the initial strips cannot be maintained.

[0078] The above comparative examples are all cases of experimental failure, which shows that any change in the preparation process will lead to experimental results that cannot meet expectations. When preparing copper-nickel-based amorphous alloys, the atomic percentage of Ni and Ti elements should be controlled between 25% and 40%, otherwise the prepared strips will be brittle; electrochemical dealloying should pay attention to controlling the concentration ratio of the corrosive solution, the current density and the dealloying time, otherwise it will be difficult to obtain a nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material with uniform surface nanoporous structure and excellent flexibility. Only by strictly controlling the parameters of each process link can we successfully obtain a nanoporous bimetallic copper-nickel alloy-copper-nickel oxide electrode material with excellent electrochemical properties and flexibility.

[0079] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A highly flexible nanoporous copper-nickel-copper-nickel oxide material, characterized in that: The material is composed of a copper-nickel-based amorphous alloy and a nanoporous bimetallic copper-nickel alloy-copper-nickel oxide layer; the copper-nickel-based amorphous alloy is used as an intermediate core layer; nanoporous bimetallic copper-nickel-copper-nickel oxide layers are arranged on both sides of the intermediate core layer; the copper-nickel-based amorphous alloy is composed of Ti x Ni x Cu 50-x Zr 50-x , wherein the subscripts are the atomic percentages of the elements, and x is 25 to 40; the bimetallic copper-nickel alloy is a Cu3.8Ni alloy, and the composition of the copper-nickel oxide is a mixture of NiO and Cu2O.

2. The highly flexible nanoporous copper-nickel-copper-nickel oxide material according to claim 1, characterized in that: The thickness ratio of the copper-nickel based amorphous alloy and the nanoporous bimetallic copper-nickel alloy-copper-nickel oxide layer is (2-3):

1.

3. The method for preparing the highly flexible nanoporous copper-nickel-copper-nickel oxide material according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) Preparation of copper-nickel based amorphous alloy strips: According to the composition of the copper-nickel-based amorphous alloy, Ni, Cu, Zr and Ti metals are mixed and smelted evenly to obtain a Ti-Ni-Cu-Zr alloy ingot; the obtained alloy ingot is heated to a molten state, and the alloy liquid is blown out by an inert gas, so that the molten liquid metal solidifies on a rotating copper roller to obtain a copper-nickel-based amorphous alloy strip; (2) Preparation of nanoporous bimetallic nickel-copper alloy-nickel-copper oxide by electrochemical dealloying: The nickel-copper based amorphous alloy strip is placed in an acid solution for electrochemical dealloying, and then taken out for cleaning to obtain the alloy.

4. The preparation method according to claim 3, characterized in that: The purity of the Ni, Cu, Zr and Ti metals is 99.9 wt.%.

5. The preparation method according to claim 3, characterized in that: The rotation speed of the copper roller is 34-36 m / s.

6. The preparation method according to claim 3, characterized in that: The copper-nickel-based amorphous alloy strip has a thickness of 20 to 50 μm and a width of 1.5 to 2 cm.

7. The preparation method according to claim 3, characterized in that: The acid solution is a mixture of H3PO4 and NH3F, wherein the concentration of NH3F is 0.2-0.5M, the concentration of H3PO4 is 0.2-0.5M; and the molar ratio of H3PO4 to NH3F is 1:

1.

8. The preparation method according to claim 3, characterized in that: The electrochemical dealloying adopts a three-electrode system, in which the nickel-copper-based amorphous alloy strip, Ag / AgCl and platinum mesh are used as the working electrode, the reference electrode and the counter electrode respectively, and the dealloying current density is 5-20 mA cm -2 The dealloying time is 30 to 120 minutes.

9. The preparation method according to claim 3, characterized in that: The dealloying current density is 10 mA cm -2 , the dealloying time is 60min.

10. Use of the highly flexible nanoporous copper-nickel-copper-nickel oxide material according to any one of claims 1 to 2 or the highly flexible nanoporous copper-nickel-copper-nickel oxide material obtained by the preparation method according to any one of claims 3 to 9 as a supercapacitor electrode material.

Citation Information

Patent Citations

  • Method for preparing nano Cu3.8 Ni alloy loaded on graphene by liquid phase reduction method

    CN104475753A

Cited By

  • Seawater conductivity sensor electrode material based on copper-nickel-based nanostructure and preparation method of seawater conductivity sensor electrode material

    CN120468232A